Conceptualising 'Disaster Education' - Kaori Kitagawa (MDPI AG, 2021)
'Disaster education' has been studied in various disciplines such as disaster risk management and environmental studies. However, disaster education is a relatively 'new enquiry' in the field of education. Particularly, the literature that conceptualises 'disaster education' in education is minimal. This paper aims to fill this gap by synthesising existing disaster education literature linking them with educational concepts. The paper suggests three possible conceptualisations for disaster education. The first is based on a temporal distinction between education undertaken in usual times or unusual times. The second conceptualisation applies modes of learning and teaching: formal, non-formal and informal. Thirdly, establishing disaster education as a sub-discipline in the field of education is proposed: one sub-discipline is lifelong learning and the other is public pedagogy. Critiquing each method of conceptualisation, the paper argues for the suitability and usefulness of locating 'disaster education' within public pedagogy.